Agricultural intensification, deforestation, and the environment: assessing tradeoffs in Sumatra, Indonesia - Tomich, Thomas P.; Noordwijk, Meine van; Budidarsono, S.; Gillison, A.N.; Kusumanto, T.; Murdiyarso, Daniel; Stolle, F.; Fagi, A.M. (CAB International, 2001)
The key hypotheses underlying ASB research in Indonesia has been intensifying land use as an alternative to slash and burn can simultaneously reduce deforestation and reduce poverty. The intensification hypothesis hinges on the existence of opportunities to raise the productivity of smallholder systems at the forest margins without degrading forest function. Estimates of returns to land and labor presented in this chapter indicate that from a purely private perspective, returns to forest conversion are high in Sumatra's peneplains. Because all derived land uses are inferior to natural forest, based on global environmental concerns, ASB research in Indonesia has shown that land use changes involve tradeoffs between these environmental concerns and the objectives of poverty alleviation and national development. If there is no action on these tradeoffs, by identifying workable options either to change incentives for conversion or to restrict access to the remaining natural forests, thus rain forests will continue to disappear. This research also provides evidence that land-use alternatives differ significantly in their ability to substitute for the global environmental services provided by natural forests. So, although forest conversion has the largest negative effect on these environmental services, the alternative land uses matter too. Carbon stocks are similar for long rotation tree-based systems, which are superior to all other land uses by this criterion except for natural forest themselves. Similarly, alternative land uses also differ significantly in their potential for biodiversity conservation, ranging between the extremes of smallholder ’complex, multistrata agroforestry systems and large-scale plantation monoculture. While there may be a tradeoff between potential profitability and biodiversity in tree-based production systems, this requires further verification. There may be little or no tradeoff between policy makers' objectives and those of smallholder households appears to be comparable to that of large-scale estates, however, this also requires further verification. There are also important institutional questions that must be addressed to enable widespread adoption of profitable alternatives by smallholders. To obtain estimates of regional or global impacts directly from measures, it is necessary to assume independence and hence addivity across space. This assumption is reasonable for some measure, but it is only a rough approximation for others. Among these measures biodiversity is the most sensitive to scaling issues. While the agronomic sustainability measure used here concerns only on-site, field level effects, the extent and spatial arrangement of land-use alternatives also produce environmental externalities. One of the key challenges of future research is to be able to asses these phenomena at the landscape level. Ultimately, instead of single land-use system or technology, the most attractive way to achieve the multiple objectives is likely to come from combinations of complementary land-use practices within a varied landscape.